Spaces of contention spatialities and social movements - Nicholls, Walter; Beaumont, Justin; Miller, Byron A. 1957- (Ashgate, 2013)
"As social movements have become more complex, geographers are increasingly studying the spatial dynamics of collective resistance and sociologists and political scientists increasingly analyzing the role of space, place and scale in contentious political activity. Occupying a position at the intersection of these disciplinary developments, this book brings together leading scholars to examine how social movements have employed spatial practices to respond to and shape changing social and political contexts. It is organised into three main sections: (1) Place, Space and Mobility: sites of mobilization and regulation, (2) Scale and Territory: structuring collective interests, identities, and resources, and (3) Networks: connecting actors and resources across space. It concludes by suggesting that different spatialities (place, scale, networks) interlink within one another in particular instances of collective action, playing distinctive yet complementary roles in shaping how these actions unfold in the political arena. By mapping state of the art conceptual and empirical terrain across Geography, Sociology, and Political Science, 'Spaces of Contention' provides readers with a much needed guide to innovative research on the spatial constitution of social movements and how social movements tactically and strategically approach and produce space"--Publisher.